Assessment of dual inhibitory activity of epifriedelanol isolated from Cayratia trifolia against ovarian cancer (Bangladesh Journal of Pharmacology, 2016)
Cayratia trifolia is used as diuretic, in tumors, neuralgia and splenopathy. However, compounds depicting anti-ovarian cancer activities from this plant source have not yet been identified and structurally characterized till date. In the present study, X-ray structure of epifriedelanol, a bioactive compound, isolated from the ethanolic extract of the C. trifolia and its binding affinities against a few proteins (HER2, EGFR and CXCR4) that are reported to get overexpressed under ovarian cancer had been thoroughly studied by using molecular docking means. Binding affinities of the compound vis-à-vis that of carboplatin, a FDA approved drug to the ovarian cancer, to interact with the protein targets are quite impressive. The drug-likeness properties of the epifriedelanol and scope to develop the compound as a potent anti-ovarian cancer drug are discussed in this paper.